Gestión del liderazgo y valores en el Colegio Nacional Técnico 22 de Marzo del cantón San Lorenzo, provincia de Esmeraldas, durante el año lectivo 2011-2012 - Medina Valencia, Baulio (2013)
The main objective of this research was: to analyze the ability of management and integrated personal and institutional values and enable fundamentally contribute to raising the quality of education in schools leadership. Exploratory methodology was applied and descriptive. The instruments used were: surveys (questionnaires) to managers, teachers, students and parents as well as interviews with managers. The sample was 66 persons of both sexes and various ages. As far as management is concerned, for good institutional management as there are shortcomings: lack of some management tools, lack of coordination between the authorities and the teams, all of which must be corrected to strengthen the institution. Leadership also suffers from administrative errors, where teachers, students and parents of families. As for values , there needs to be more communication at all levels and to implement certain values such as responsibility, solidarity, respect, discipline.